Piezo-phototronic effect regulated broadband photoresponse of a-Ga2O3/ZnO heterojunction. Issue 15 (28th March 2023) - Wang, Jiantao; Zhou, Yan; Wang, Zihan; Wang, Boying; Li, Yongqiu; Wu, Banghao; Hao, Chunlin; Zhang, Yaju; Zheng, Haiwu
Abstract : A flexible a-Ga2 O3 /ZnO heterojunction photodetector demonstrates a broadband response range from the deep ultraviolet (265 nm) to the near-infrared (1060 nm) and a bidirectional adjustable photocurrent response via the piezo-phototronic effect. Abstract : Amorphous Ga2 O3 (a-Ga2 O3 ) films have attracted considerable attention in the field of photodetectors due to their excellent optical absorption response and photoelectric properties. However, there are few studies that have utilized the piezo-phototronic effect to regulate the broadband photoresponse of Ga2 O3 -based photodetectors. Here, a flexible a-Ga2 O3 /ZnO heterojunction was constructed, which demonstrated a broadband response range from deep ultraviolet (265 nm) to the near-infrared (1060 nm) and realized a bidirectional adjustable photocurrent response via the piezo-phototronic effect. Under 265 nm illumination and 0.5 V bias, the responsivity and detectivity of the a-Ga2 O3 /ZnO heterojunction reached up to 12.19 A W −1 and 4.71 × 10 11 Jones under 0.164% compressive strain, corresponding to enhancements of 67.7% and 66.8% compared to those under a strain-free state, respectively. Moreover, the broadband photoresponse of the a-Ga2 O3 /ZnO heterojunction beyond the bandgap limit was tunable under bidirectional strain. The working mechanism of photoresponse performance for the a-Ga2 O3 /ZnO heterojunction at different wavelengths was elucidated in detail. Oxygen vacancy-assisted carrier generation was found to be influenced by the wavelength of incident light, which mainly determined the broadband photoresponse of the heterojunction. The modulation of the a-Ga2 O3 /ZnO heterojunction photodetector was interpreted in light of the strain-induced regulation of the barrier height. This work represents an important step toward the development of adjustable broadband photodetectors based on a-Ga2 O3 films.